2014
DOI: 10.1007/s10719-014-9543-9
|View full text |Cite
|
Sign up to set email alerts
|

Antithrombin-binding oligosaccharides: structural diversities in a unique function?

Abstract: Heparin-antithrombin interaction is one of the most documented examples of heparin/protein complexes. The specific heparin sequence responsible for the binding corresponds to a pentasaccharide sequence with an internal 3-O-sulfated glucosamine residue. Moreover, the position of the pentasaccharide along the chain as well as the structure of the neighbor units affects the affinity to antithrombin. The development of separation and purification techniques, in conjunction with physico-chemical approaches (mostly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 55 publications
0
24
0
Order By: Relevance
“…The currently known AT-binding sequence comprises a disaccharide –GlcA-GlcNS3S±6S-unit 34 (Supplementary Fig S3). The substitution of the –GlcA-GlcNS3S6S- disaccharide unit with the –IdoA2S-GlcNS3S6S- disaccharide unit in HS was perceived to abolish AT-binding affinity 3536 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The currently known AT-binding sequence comprises a disaccharide –GlcA-GlcNS3S±6S-unit 34 (Supplementary Fig S3). The substitution of the –GlcA-GlcNS3S6S- disaccharide unit with the –IdoA2S-GlcNS3S6S- disaccharide unit in HS was perceived to abolish AT-binding affinity 3536 .…”
Section: Resultsmentioning
confidence: 99%
“…The AT-binding sequences isolated so far all consist of the –GlcA-GlcNS3S6S- disaccharide repeating unit, which is a product of 3-OST-1 enzyme modification 34, 40 . Although Compound 5 , which is a product of 3-OST-3 enzyme modification, does not contain the –GlcA-GlcNS3S6S- disaccharide unit, it binds to AT and displays anticoagulant activity.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, other types of carbohydrate structures, distinct from GAGs, including those with low or no activity, have also been identified that can fulfil the structural requirements of AT binding [72] and a proposal has been made that the stabilization of AT is the key determinant of its activity [73]. It has also been shown that N-acetylation or N-sulfation is permitted in the substitution pattern of residues adjacent to and within, the first glucosamine residue, the pentasaccharide and that specific residues outside of the pentasaccharide region active for AT can influence AT activity [74][75][76][77][78]. This reinforces the idea that binding, even with low affinity, does not necessarily equate to activity.…”
Section: Antithrombin-heparin Pentasaccharide: An Exception That Doesmentioning
confidence: 99%
“…[2]) this sequence was reproduced by total chemical synthesis, which led to the anticoagulant drug Fondaparinux and several follow up compounds. [3,4] The availability of homogeneous synthetic compounds allowed X-ray crystallography [5][6][7][8] and NMR studies [9][10][11][12][13][14] for ap lethora of heparinb inding oligosaccharides. All these results supported the strict specificity of the AGA*IA sequence in the heparin-AT recognition.B ased on theses tudies and on enzyme kinetics,a modelw as proposed to explain the two-stepA Tb inding and activation by heparin.…”
Section: Introductionmentioning
confidence: 99%